Effects of Permaculture Practices on Soil Physicochemical Properties and Organic Matter Distribution in Aggregates: A Case Study of the Bec-Hellouin Farm (France) - de Tombeur, Felix; Sohy, Valentin; Chenu, Claire; Colinet, Gilles; Cornelis, Jean-Thomas (Frontiers in Environmental Science, 2018)
The limitations of conventional agriculture have accelerated the need for a transition to an environmentally and economically sustainable agricultural model. In this regard, the role played by soil organic matter (SOM) is key. Here, we aimed to study the impact of permaculture and biointensive micro-gardening practices, characterized by intensive cultivation, the use of large and localized organic inputs and the non-use of mineral fertilizers and pesticides, on soil physico-chemical properties and SOM distribution in aggregate-size fractions. The physico-chemical properties of soils in permaculture farming implemented for seven years were compared with a soil under pasture. A soil experiencing conventional agriculture practices in similar geopedoclimatic conditions was simultaneously studied. Soils were separated into four aggregate-size fractions, into which organic carbon (OC) concentrations have been measured. The major soil physico-chemical properties were measured on the bulk soils. The concentrations of total OC and nitrogen (N) in bulk soils were higher under permaculture practices, due to significant inputs of manure and compost, resulting in higher concentrations of the bioavailable nutrients Ca, Mg, K and P. The permaculture practices sustained a level of macroaggregation similar to that of the pasture, and well above that of conventional practices. OC concentrations increased in the 250-2000 µm, 50-250 µm and occluded 50-250 µm fractions, but not in the <50 µm fraction compared to pasture. This can be explained by the too short duration of permaculture practices for allowing the decomposition of coarse particulate organic matter (POM) into fine sized SOM that is more associated with mineral particles in free clay and silt size fraction. The higher OC stocks in permaculture are therefore mainly governed by the coarse POM fraction. Our results show that permaculture/biointensive micro-gardening practices enhance SOM storage and modify the distribution of SOM in aggregate size fractions, while substantially improving nutrient bioavailability and suggests that permaculture practices strongly affect soil properties. The effects of permaculture practices on soil properties would certainly vary depending on geopedoclimatic context, justifying the need to implement the approach for other soil types. Finally, we recommend to compare biogeochemical budget and nutrients use efficiency of permaculture gardening with conventional horticulture gardening.